Demythiser le folklore dans les nouvelles de Ioan Slavici (The Demythisation of Folklore in Ioan Slavici’s Short Stories) - Mihai-Alin Gherman (Incursiuni în imaginar)
Ioan Slavici’s memoirs underline the impact the folklore had on his childhood (as for all the great Romanian classics in general). The environment described is the one of the fair, whose type of organization was beginning to follow other rules and principles than those of the village, without giving up the influences of rural civilization though. Even if he got in touch with cities as Vienna, Sibiu or Bucharest, Slavici continued to create a cultural symbiosis between the city and the village. This paper’s goal is to underline some of these aspects with a stress on the conscious or unconscious reception of the folklore vectors in his work.